2017
DOI: 10.1007/s00335-017-9717-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in bone structure and unloading-induced bone loss between C57BL/6N and C57BL/6J mice

Abstract: The C57BL/6 mouse, the most frequently utilized animal model in biomedical research, is in use as several substrains, all of which differ by a small array of genomic differences. Two of these substrains, C57BL/6J (B6J) and C57BL/6N (B6N), are commonly used but it is unclear how phenotypically similar or different they are. Here, we tested whether adolescent B6N mice have a bone phenotype and respond to the loss of weightbearing differently than B6J. At 9 weeks of age, normally ambulating B6N had lower trabecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 58 publications
4
16
0
Order By: Relevance
“…We speculate that ovariectomy induced bone loss recapitulates age‐related trabecular bone deterioration patterns, reported to be more severe in the metaphyseal region of the long bones than the vertebral body in C57BL/6J mice . These results are consistent with those reported previously . To examine the mechanism, we looked at OB and OC by histology.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We speculate that ovariectomy induced bone loss recapitulates age‐related trabecular bone deterioration patterns, reported to be more severe in the metaphyseal region of the long bones than the vertebral body in C57BL/6J mice . These results are consistent with those reported previously . To examine the mechanism, we looked at OB and OC by histology.…”
Section: Discussionsupporting
confidence: 89%
“…22 These results are consistent with those reported previously. 60,61 To examine the mechanism, we looked at OB and OC by histology. Our finding of increased OB and decreased OC in the proximal tibia or L6 spine of MRL/MpJ mice compared to C57BL/6J mice indicates that MRL/MpJ mice are able to maintain bone mass by a mechanism of accelerated bone formation and reduced bone resorption during osteoporosis development following ovariectomy surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We then performed a 30-day HU study under these social housing conditions, side-by-side with animals maintained according to the standard NASA single housing HU system (Figure 1). Animals selected for this study were female C57BL/6NJ mice shown previously to be sensitive to bone loss caused by HU (Sankaran et al, 2017). Controls (normally loaded, NL) were age- and sex-matched animals freely ambulating in standard mouse cages.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies show cancellous bone loss begins in early adulthood in C57BL/6 mice (2-3month-old), earlier than that of BMD 23,24,46 . Notably, different mouse strains exhibit different patterns in bone loss [47][48][49] . C57BL/ 6J mice experience bone loss as early as 2 months of age, while BALB/c mice wouldn't show significant reduction until 7 months 50 .…”
Section: Discussionmentioning
confidence: 99%